2004
DOI: 10.1038/sj.bdj.4811353
|View full text |Cite
|
Sign up to set email alerts
|

Puncture resistance and stiffness of nitrile and latex dental examination gloves

Abstract: ObjectiveThe aim of the current study was to assess the puncture resistance and stiffness of nitrile and latex dental examination gloves. Methods Puncture resistance was measured by employing an adapted version of ASTM F1342-91 using both a 316 stainless steel puncture probe (0.8 mm diameter) and a dental injection needle (0.45 mm diameter) interfaced to a tensile testing apparatus. Glove specimens (12 cm length, 1.5 cm breadth) were removed for modulus (M100) evaluation by assessing the force required to elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, there is a wide variation in the properties of gloves made from different materials and by different manufacturers. Research studies found, for example, that the performance of vinyl gloves was significantly inferior to that of latex and nitrile gloves in terms of barrier protection, 9 11 durability, 12 and resistance to tear 13 , 14 . Nitrile gloves have been found to be comparable to latex gloves in barrier protection, 11 puncture resistance, 14 and durability 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a wide variation in the properties of gloves made from different materials and by different manufacturers. Research studies found, for example, that the performance of vinyl gloves was significantly inferior to that of latex and nitrile gloves in terms of barrier protection, 9 11 durability, 12 and resistance to tear 13 , 14 . Nitrile gloves have been found to be comparable to latex gloves in barrier protection, 11 puncture resistance, 14 and durability 15 .…”
mentioning
confidence: 99%
“…Research studies found, for example, that the performance of vinyl gloves was significantly inferior to that of latex and nitrile gloves in terms of barrier protection, 9 11 durability, 12 and resistance to tear 13 , 14 . Nitrile gloves have been found to be comparable to latex gloves in barrier protection, 11 puncture resistance, 14 and durability 15 . However, nitrile gloves have less elasticity, 11 , 15 resulting in reduced dexterity for fine motor skills as compared to latex gloves 15 .…”
mentioning
confidence: 99%
“…Previous studies found nitrile gloves to be comparable to latex gloves in terms of barrier protection, durability, and resistance to puncture . However, nitrile gloves have less elasticity, resulting in reduced dexterity for fine motor skills, as compared to latex gloves .…”
Section: Glove Permeabilitymentioning
confidence: 98%
“…Nitrile gloves due to their latex-free chemical make-up and variable levels of thickness offer adequate protection against many solvents and chemicals Moreover, they are reported to exhibit better puncture resistance in contrast to the latex gloves. [ 7 ]…”
Section: Final Phase: Personal Protection Treatment Strategies Disimentioning
confidence: 99%